2020
DOI: 10.1093/asj/sjz364
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Subcutaneous Radiofrequency After Liposuction: A New Application for Face and Neck Skin Tightening

Abstract: Background Minimally invasive or noninvasive skin-tightening procedures have become trends in facial and neck rejuvenation. Radiofrequency-assisted liposuction (RFAL) is a new choice for the treatment of skin relaxation that is more effective than noninvasive surgery without surgical incision. Objectives The authors recommend a 2-step method in which radiofrequency is applied after appropriate liposuction is performed. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…These technologies include a variety of ultrasonic devices and RF devices. [8][9][10][11][12][13][14][15] In this author's clinical practice several categories of devices are available, so in many instances a skin tightening device and a resurfacing device may be used at the time of a facelift. It has been found that both transcutaneous RF microneedling devices and percutaneous RF devices are helpful.…”
Section: Skin Resurfacing and Skin Tightening Technologiesmentioning
confidence: 99%
“…These technologies include a variety of ultrasonic devices and RF devices. [8][9][10][11][12][13][14][15] In this author's clinical practice several categories of devices are available, so in many instances a skin tightening device and a resurfacing device may be used at the time of a facelift. It has been found that both transcutaneous RF microneedling devices and percutaneous RF devices are helpful.…”
Section: Skin Resurfacing and Skin Tightening Technologiesmentioning
confidence: 99%
“…53 Radiofrequency devices are frequently promoted as a "nonexcisional" alternative to a facelift, 14,25 even simulating the effect of a facelift. 37 Surgery is often described as invasive or excisional. Radiofrequency, unlike ultrasound, which was a previous energy-based treatment, does not specifically target fat.…”
Section: Comparison With Surgical Resultsmentioning
confidence: 99%
“…Radiofrequency devices are frequently promoted as a “nonexcisional” alternative to a facelift, 14,25 even simulating the effect of a facelift 37 . Surgery is often described as invasive or excisional.…”
Section: Discussionmentioning
confidence: 99%
“…They had larger acceptance, but the aesthetic outcomes are relatively modest compared with those of the excisional surgeries. [2][3][4][5][6][7] Radiofrequency-assisted liposuction (RFAL) was first introduced in 2009 for body contouring and skin tightening. The major principle of RFAL is to use radiofrenquency's effect on the fibro-septal network to achieve skin tightening and soft tissue contraction.…”
Section: Introductionmentioning
confidence: 99%